ANALISIS BIOMETRI DAN STRUKTUR POPULASI KERANG HIJAU (Perna viridis) DALAM BAGAN TANCAP DI LAUT BANYUURIP KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - Rifqi Fauzi; Farikhah; Nur Maulida Safitri (Techno-Fish, 2022)
Green mussel (Perna viridis) is one of the marine resource commodities with great potential that needs to be exploited in the Banyuurip Sea, owing to its ample availability throughout the year and limited exploration. The purpose of this study was to analyze biometry, class size distribution, length—weight relationship, and condition index of green mussels in the Banyuurip Sea, Banyuurip Village, Ujungpangkah District, Gresik Regency. This study employs a descriptive method, with five stake cultures chosen through purposive sampling. During the study period from June-August 2021, 20 samples (from a total 300 biota) were collected at each station for 20 days on the five stake cultures investigated. The findings of biometric measures taken during the study revealed that the value of the class size distribution variable in the Stake I had 7 classes, the Stake II had 6 classes, the Stake III had 9 classes, the Stake IV had 6 classes, and the Stake V had 7 classes. The value of 'b' morphometry and the length—weight relationship of green mussels (L-b) 0.77, (L-w) 0.39, (L-tw) 1.69, (L-ww) 1.71. The index value of the condition of the green mussels on the Stake I (30.94±2.12), the Stake II (31.45±3.24), the Stake III (31.39±5.49), the Stake IV (32.82±4.39), and the Stake V (33.44±5.48).